THE USE OF ENGLISH VIDEO PODCASTS TO IMPROVING STUDENT’S LISTENING SKILL AT STKIP BUDIDAYA BINJAI - Silfana, Silfana; Panjaitan, Efrini; Indari, Ayu (Institut Pendidikan Tapanuli Selatan, 2025)
Listening skills are an important aspect of English language learning that supports students' communication skills. However, students often face difficulties in understanding pronunciation, vocabulary, intonation, and conversational context, especially when listening to native speakers. This study aims to identify the main weaknesses in students' listening skills and understand their perceptions of the challenges they face. This study used a mixed-method approach, combining qualitative and quantitative methods involving 45 students of the English Education Study Program at STKIP Budidaya Binjai who were selected through purposive sampling. Data was collected through questionnaires to measure students' perceptions of their listening skills, as well as to explore the experiences and obstacles they face during the listening process. The results of this study are expected to provide insight into the main challenges experienced by students, as well as the basis for developing more effective and engaging learning media, such as the integration of podcast videos or other interactive methods, to improve students' listening skills in a sustainable manner.